Efficacy, selectivity and economics of metolachlor for weed controlin maize (Zea mays) and its effect on succeeding chickpea (Cicer arietinum) - JOSHI, NEESHU; JOSHI, SHOURABH; SINGH, SAMARPAL; PRAMANICK, BISWAJIT; JINGER, DINESH; SHARMA, JITENDRA KUMAR; JOSHI, EKTA; SHEKHAWAT, HARSH VARDHAN SINGH (The Indian Journal of Agricultural Sciences, 2025)
The inverse correlation between maize (Zea mays L.) yield and weed density has been well-established over time. Among the various weed management strategies, chemical control is recognized as the most efficacious. An experiment was conducted during 2019 and 2020 at Agriculture Research Sub-Station (Agriculture University, Jodhpur, Rajasthan), Sumerpur, Pali, Rajasthan to evaluate superiorr effectiveness of metolachlor @1000 g a.i./ha and 1200 g a.i./ha in managing broad-leaved weeds and certain grass species, when compared to atrazine applied at 1000 g a.i./ha, in maize cultivation. The maize variety ‘PHM-4’ was selected for the study. The experiment was laid out in a randomized block design (RBD) having three replication. This resulted in a total weed control efficiency of 63.4% and 61.3% across all crop growth stages. However, it's worth noting that a higher dose of metolachlor at 2000 g a.i./ha showed signs of phytotoxicity on maize, which eventually recovered within 15–20 days post-herbicide treatment. The study concluded that metolachlor at 1000 g a.i./ha effectively combats broad-leaved and some grassy weeds in maize. Notably, the maximum net return was observed with metolachlor at 1000 g a.i./ha, amounting to ₹35,150/ha and ₹51,496/ha during both years. In the subsequent chickpea phase, no treatment was applied, and phytotoxicity was observed in metolachlor at 2400 g a.i./ha, causing yellowing and stunting of plants.